Effect the Nanoparticles of Fe2O3 and CuO to Increasing the Activity of Sulfadiazine Against Multidrug Resistant Pseudomonas Aeruginosa: Pengaruh Nanopartikel Fe2O3 dan CuO untuk Meningkatkan Aktivitas Sulfadiazin Terhadap Pseudomonas Aeruginosa yang Resisten Terhadap Berbagai Jenis Obat - Ali Jaffar Saleem (Academia Open, 2024)
General Background: Antibiotic resistance is a critical global health issue, and innovative approaches are needed to combat multidrug-resistant (MDR) bacteria. Specific Background: Nanotechnology has emerged as a promising strategy to enhance antibiotic efficacy and reduce resistance. Knowledge Gap: However, there is limited understanding of how metal oxide nanoparticles (NPs) like Fe2O3 and CuO can be utilized to improve the performance of antibiotics such as sulfadiazine. Aims: This study aimed to synthesize Fe2O3 and CuO nanoparticles, conjugate them with sulfadiazine, and evaluate their antibacterial efficacy against MDR Pseudomonas aeruginosa. Results: The nanoparticles were synthesized via chemical precipitation, with Fe2O3 and CuO having mean crystal sizes of 41.40 nm and 44.83 nm, respectively. When bound to sulfadiazine, the crystal sizes were 42.62 nm (Fe2O3) and 38.77 nm (CuO). The minimum inhibitory concentration (MIC) values for sulfadiazine-bound CuO and Fe2O3 NPs ranged from 16-32 μg/ml, significantly lower than the 64-128 μg/ml observed for standard sulfadiazine. Hemolysis assays confirmed the biocompatibility of these nanocomposites at tested concentrations. Novelty: The study reveals that Fe2O3 and CuO nanoparticles significantly enhance sulfadiazine's antibacterial activity against MDR P. aeruginosa, suggesting a potential method to bypass traditional resistance mechanisms. Implications: The study suggests that nanoparticle-conjugated antibiotics could be a promising solution for combating antibiotic resistance, potentially reducing its negative impact on public health. Highlights: Nanoparticles reduce sulfadiazine's MIC against MDR Pseudomonas aeruginosa. Fe2O3 and CuO nanoparticles enhance antibiotic efficacy. Hemolysis assays confirm nanocomposites' safety and biocompatibility. Keywords: Nanotechnology, Antibiotic Resistance, Fe2O3 Nanoparticles, CuO Nanoparticles, MDR Pseudomonas aeruginosa